(untitled) (Polifonia, 2018)
Polifonia / Estudos linguísticos [recurso eletrônico]. – v. 25, nº 38.1 (maio-agosto. 2018). – Cuiabá: UFMT, Programa de Pós- Graduação em Estudos de Linguagem, 2018, 192p.